Exposição de culturas de fibroblastos de pterígios primários e recidivados à mitomicina c e ao 5-fluorouracil - Viveiros, Magda Massae Hata [UNESP] (2006)
Purpose: To evaluate the proliferation of the fibroblasts from primary and recurrent pterygium in culture of cells, after the exposure to mitomycin C and to 5-fluorouracil. Methods: Cultures of fibroblasts from primary and recurrent pterygiuns had been carried through. The cells of the third passage were exposed to mitomycin C 0.4% during 3 minutes and to 5-fluorouracil 25mg/ml that was kept in the nutritional medium. After 3, 6, 12 and 18 days of the exposure, cell countings were made in hemocytometer, in triplicate, with a control not treated with the drugs for each day. The data were submitted to statistical analysis.Results: Mitomicyn C had homogeneous behavior in the primary and recurrent groups, which inhibited the cellular proliferation since the first counting day. However, with 5-fluorouracil, the proliferation inhibition was verified only after the third day of evaluation (in the second counting day) in the recurrent group, and since the first counting day in the primary group. At the end of the experimental period, 5-fluorouracil and mitomycin C were equally efficient in the inhibition of the fibroblasts from primary and recurrent pterygium proliferation. In the controls not exposed, the cell's numbers were increasing during the experimental time.Conclusion: Mitomycin and 5-fluorouracil are equally able to inhibit fibroblasts proliferation from primary and recurrent pterygium Tenon's capsule in cell culture.